2016
DOI: 10.5820/aian.2303.2016.248
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurship education: A strength-based approach to substance use and suicide prevention for American Indian adolescents

Abstract: American Indian (AI) adolescents suffer the largest disparities in substance use and suicide. Predominating prevention models focus primarily on risk and utilize deficit-based approaches. The fields of substance use and suicide prevention research urge for positive youth development frameworks that are strength based and target change at individual and community levels. Entrepreneurship education is an innovative approach that reflects the gap in available programs. This paper describes the development and eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 59 publications
0
23
0
Order By: Relevance
“…Currently, there is limited research on community-based interventions in the U.S. that address economic disparities as they relate to HIV. The experimental intervention draws from prior published HIV prevention microenterprise interventions conducted primarily in low-income countries and targeting women [13,[44][45][46][47][48][49][50][51][52]. We have adapted these models for use in an impoverished U.S. urban setting with a focus on both African-American women and men.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, there is limited research on community-based interventions in the U.S. that address economic disparities as they relate to HIV. The experimental intervention draws from prior published HIV prevention microenterprise interventions conducted primarily in low-income countries and targeting women [13,[44][45][46][47][48][49][50][51][52]. We have adapted these models for use in an impoverished U.S. urban setting with a focus on both African-American women and men.…”
Section: Discussionmentioning
confidence: 99%
“…It is based on prior qualitative formative research conducted by the PI that examined health-focused entrepreneurial education [40,41], cell phone behaviors [42], uptake of text message surveys, and behavioral economics relating to sexual risk behaviors [43] in young adults experiencing homelessness. It is also based on prior published microenterprise interventions for HIV risk reduction used primarily in low-income countries, and adapted for use in a U.S. urban minority setting [13,[44][45][46][47][48][49][50][51][52]. Participants assigned to the experimental intervention will receive the following:…”
Section: Experimental Interventionmentioning
confidence: 99%
“…We also conducted focus groups and in-depth interviews to collect qualitative data with a subset of youth who participated in ABG. A detailed description of the study rationale, methods including a CONSORT diagram illustrating the study flow, and baseline characteristics of participants may be found elsewhere [41,42]. The study design was reviewed and approved by the Apache Tribal Council and Health Advisory Board, and the JHU Institutional Review Board (IRB) (#5616).…”
Section: Methodsmentioning
confidence: 99%
“…The purpose of this paper is to report on entrepreneurship, economic, and social well-being outcomes from the 5-year RCT of ABG (#NCT02157493; clinicaltrials.gov). The original aims of the study were to longitudinally evaluate ABG for impacts on: (1) Adolescent behavioral and mental health outcomes, including substance use, suicide, and violence to self and others; (2) social well-being; (3) educational; and (4) entrepreneurship/economic outcomes [41,42]. This paper focuses on outcomes from aims 2 and 4.…”
Section: The Purpose Of This Papermentioning
confidence: 99%
See 1 more Smart Citation